(untitled) (Journal of the College of Languages (JCL), 2025)
The study conducted a pragmatic analysis of Nigeria’s re-introduced national anthem, “Nigeria, We Hail Thee”, in order to examine the communicative functions of the anthem and the ways in which language was used to convey national identity, unity, and duty. Using a mixed-method approach through Searle’s Speech Act and Halliday’s Systemic Functional Linguistics theories, a qualitative line-by-line analysis was first performed, before categorizing the locutionary, illocutionary, and perlocutionary acts, which were analysed quantitatively. The study showed distinct speech acts, including admiring, asserting unity, and encouraging duty, asserting values, declaring, promising, committing, and praying. Statistical analysis of the frequency of illocutionary acts revealed that “praying” was the most frequent illocutionary act, appearing in two lines (25%), while other acts, such as “admiring” and “asserting unity,” occurred once each (12.5%). The study also examined the verbs used in the anthem, categorizing them into Austin’s typology of exercitives, behavitives, and verdictives. The analysis found that behavitives, which relate to behaviour and social conduct, dominated the anthem (50%), followed by exercitives (37.5%) and verdictives (12.5%). The findings revealed that the anthem primarily utilised speech acts that promoted national unity, service, and respect for the country’s values, with a significant focus on divine intervention and guidance.